Urban alchemy : a governance and planning framework for sustainable urban transformation in developing economies - Aigbavboa, Clinton Ohis; Cobbina, John Edward; Ametepey, Simon Ofori; Thwala, Wellington Didibhuku (Emerald Publishing Limited, 2025)
Urban Alchemy delves into the pressing challenges and unique opportunities facing developing countries in their quest for sustainable urban transformation. Readers are introduced to a comprehensive framework designed to guide policymakers, urban planners, and scholars in reimagining the future of cities. The chapters the book further strengthens the importance of academic and policy debate on urban governance and planning in the Sustainable Urban Transformation (SUT) process in developing countries through an extensive review of the literature on initiatives in developed or post-industrialized cities. The book contributes to the body of knowledge by providing an understanding of how governance and planning with other variables can help in achieving the SUT agenda in developing countries. It also opens up further academic discussion and motivates policymakers to develop policies and initiatives aimed at the creation of a better life for its citizens now and for future generations, inspiring a new era of sustainable urban planning.
Includes index.
Keywords: City planning.; Architecture -- Urban & Land Use Planning.; City and town planning: architectural aspects.; elektronické knihy; electronic books